(untitled) (Acta Scientiarum. Animal Sciences, 2018)
The objective of this study was to evaluate in situ ruminal degradability of elephant grass silages with addition of 8, 16 and 24% of faveira pods in experimental silos of 100x50 mm, equipped with bunsen valves. The content of crude protein (cp) and neutral detergent fiber (ndf) were determined on a dry matter basis. To evaluate the in situ degradability of dm, cp and ndf, nylon bags containing 4 g sample were incubated in the rumen of three fistulated cattle for 6, 24 and 72h. The dm and cp content of elephant grass silages increased (p < 0.05) from 8% inclusion associated with a higher concentration of constituents in faveira pods (77.25 and 9.61% dm). The ndf fraction reduced 10.91% (p < 0.05) when adding 24% pods. The potential degradation (pd) of dm and cp increased with inclusion of faveira pods, with 75.97 and 95.21%, respectively, for the level of 24%. There was increased potentially degradable fraction (bp) of ndf by 7.07% with inclusion of 24% faveira pods, as well as a reduced colonization time (lag) from 3.81 to 3.44 hours. The addition of up to 24% faveira pods to elephant grass silages improves rumen microbial degradation, and it is indicated this level of addition to obtain better quality silage.